Hubungan Pengetahuan Premenstrual Syndrome (PMS) dengan Tingkat Kecemasan pada Remaja - Alyah Chandra; Lucia Yovita Hendrati (Media Gizi Kesmas, 2023)
Background: A premenstrual syndrome is a group of symptoms that occur in the luteal phase of the menstrual cycle that cause disturbances in a person's work and lifestyle. Objectives: This study is to find out and describe all theories and journals of expert opinions related to the relationship of knowledge of premenstrual syndrome with the level of anxiety in adolescents and to find new ideas in research journals conducted in literature studies. Methods: This research design uses a literature review study method. The source of data in this study used secondary data. It was obtained by using a literature study of the relationship between knowledge of premenstrual syndrome by the research topic from 2016-2021 in many as 6 journals on google schooler. Results: Based on the results of this literature review, it was presented narratively to describe the results of research from 6 journals/research results that were relevant to the topic/problem of the relationship between lack of knowledge about premenstrual syndrome and anxiety levels in adolescents of the 6 journals that researchers reviewed, all of them used cross-sectional research methods or designs. Conclusions: Young women who experience premenstrual syndrome (PMS) can expand their awareness and knowledge by seeking information through print or electronic media and administering appropriate treatment to reduce anxiety.